2015
DOI: 10.1007/s00253-015-6701-3
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid production from xylose by engineered Saccharomyces cerevisiae without PDC or ADH deletion

Abstract: Production of lactic acid from renewable sugars has received growing attention as lactic acid can be used for making renewable and bio-based plastics. However, most prior studies have focused on production of lactic acid from glucose despite that cellulosic hydrolysates contain xylose as well as glucose. Microbial strains capable of fermenting both glucose and xylose into lactic acid are needed for sustainable and economic lactic acid production. In this study, we introduced a lactic acid-producing pathway int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
51
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 43 publications
3
51
0
1
Order By: Relevance
“…Considering that the isobutanol production pathway in SR8-Iso is compartmentalized in the mitochondria, it is likely that increased mitochondrial biogenesis is a major contributor to the enhanced isobutanol yields from xylose we observe. However, other physiological changes induced by xylose that could divert flux from ethanol to isobutanol production may still be taking place, which would be consistent with several examples where engineered biosynthetic pathways are enhanced by xylose utilization without involving their compartmentalization in mitochondria (S. K. Kim, Jo, Park, Jin, & Seo, 2017;Koivistoinen et al, 2013;Kwak, Kim et al, 2017;Salusjärvi et al, 2017;Turner et al, 2015). Future research to elucidate what physiological changes brought by xylose are responsible for this product biosynthesis enhancement may provide new insights to engineer strains with improved bioconversion of glucose into isobutanol and other nonethanol products.…”
supporting
confidence: 73%
“…Considering that the isobutanol production pathway in SR8-Iso is compartmentalized in the mitochondria, it is likely that increased mitochondrial biogenesis is a major contributor to the enhanced isobutanol yields from xylose we observe. However, other physiological changes induced by xylose that could divert flux from ethanol to isobutanol production may still be taking place, which would be consistent with several examples where engineered biosynthetic pathways are enhanced by xylose utilization without involving their compartmentalization in mitochondria (S. K. Kim, Jo, Park, Jin, & Seo, 2017;Koivistoinen et al, 2013;Kwak, Kim et al, 2017;Salusjärvi et al, 2017;Turner et al, 2015). Future research to elucidate what physiological changes brought by xylose are responsible for this product biosynthesis enhancement may provide new insights to engineer strains with improved bioconversion of glucose into isobutanol and other nonethanol products.…”
supporting
confidence: 73%
“…Instead of genetic perturbations for diminishing ethanol production, Turner et al introduced LDH into an efficient xylose-fermenting S. cerevisiae . They demonstrated that the engineered S. cerevisiae efficiently produces lactic acid without detectable ethanol accumulation on xylose (Y lactate/xylose  = 0.69 g/g xylose, Y ethanol/xylose  < 0.01 g/g xylose), while the engineered yeast produced lactic acid and ethanol simultaneously at 2:3 ratios on glucose (Y lactate/xylose  = 0.22 g/g glucose, Y ethanol/xylose  = 0.31 g/g glucose) [12]. Weaker metabolic activity of glycolysis on xylose [126128] is a probable interpretation of this phenomenon.…”
Section: Production Of Advanced Biofuels and Chemicals From Xylose Bymentioning
confidence: 99%
“…LDH competes with PDC for pyruvate which is the final product of glycolysis as well as the branch point metabolite between lactate and ethanol pathways. As LDH has smaller K M value than PDC [12], the inefficient glycolytic metabolism under xylose culture conditions would allow LDH to direct more metabolic flux from pyruvate than endogenous PDC. Additionally, the expression level of JEN1 , a lactate-proton symporter coding gene, is upregulated under xylose through dysregulation of glucose-dependent repression [130].…”
Section: Production Of Advanced Biofuels and Chemicals From Xylose Bymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in the case of LA production, the isolated strain Enterococcus mundtii QU 25 was engineered to produce LA from glucose: xylose mixtures . An efficient LA‐producing S. cerevisiae strain was also developed when the LA pathway was introduced in a strain able to metabolize xylose . Furthermore, by the introduction of a xylose‐metabolism pathway and further adaptive evolution, an efficient LA producer Pediococcus strain was obtained …”
Section: Introductionmentioning
confidence: 99%